2017
DOI: 10.3390/jof3020030
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Infection of Metarhizium spp. Fungus and Their Potential as Biological Control Agents

Abstract: Chemical insecticides have been commonly used to control agricultural pests, termites, and biological vectors such as mosquitoes and ticks. However, the harmful impacts of toxic chemical insecticides on the environment, the development of resistance in pests and vectors towards chemical insecticides, and public concern have driven extensive research for alternatives, especially biological control agents such as fungus and bacteria. In this review, the mode of infection of Metarhizium fungus on both terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 109 publications
0
61
0
4
Order By: Relevance
“…As such, unmodified Metarhizium spp. have not met WHO Prequalification Vector Control (WHOPES) standards for a vector control product . This is consistent with intensive efforts to use these fungi to control other pests; historically biocontrol agents have not met expectations because of low virulence, and many Metarhizium spp.…”
Section: Use Of Entomopathogenic Fungi To Control Insect Pestsmentioning
confidence: 78%
“…As such, unmodified Metarhizium spp. have not met WHO Prequalification Vector Control (WHOPES) standards for a vector control product . This is consistent with intensive efforts to use these fungi to control other pests; historically biocontrol agents have not met expectations because of low virulence, and many Metarhizium spp.…”
Section: Use Of Entomopathogenic Fungi To Control Insect Pestsmentioning
confidence: 78%
“…The fungi based biopesticides can affect the host as the insect cuticle comes in contact with the fungi during spray or during larvae movement. The fungi can then adhere to the host cuticle, germinates, form appressorium which penetrates to the insect body, colonise the haemolymph, extrudes and sporulates which finally lead to the death of the host [53]. High mortality rates of stem borer larvae were recorded in B. bassiana and M. anisopliae treated insects which were parallel with findings of Tefera [31], Terefe et al [54] who respectively reported high mortality of C. partellus and S. calamistis larvae treated with natural isolates of B. bassiana and M. anisopliae under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This isolation condition provided a suitable microclimate for the development, multiplication and penetration of the spores in the body of the insects, unlike what happened in greenhouse bioassays, where the solution was sprayed on the insects. The technique of spraying the solution on the insects provides a lower deposition of M. anisopliae on the body of the individuals, which increased the time required for the penetration of the spores inside the individuals, and consequently, the establishment of the colony in the host (MENT et al, 2010;AW;HUE, 2017). Among the isolates of M. anisoplia researched, the 08RA isolate showed the greatest pathogenicity on the bug species in a shorter period of time compared to the isolates 05RA, 11RA and 02RA.…”
Section: Discussionmentioning
confidence: 99%